Meningkatkan Kemampuan Menulis Puisi dengan Penerapan Teknik Imagine (Sugesti) Pada Peserta Didik Kelas VIII 3 SMP Negeri 8 Palembang - Hanindiya, Nur Azmi; R, Rohani; Andriyani, Irma; H, Hetilaniar (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The research conducted by the researcher was Classroom Action Research. This research aims to determine the improvement in student learning outcomes through the Imagine (Suggestion) technique in class VIII 3 poetry writing material at SMP Negeri 8 Palembang. The data collection techniques used in this research are interviews, observation, learning results and documentation. The steps taken in this research were interviews with Indonesian language teachers to find out the students' problem points in writing poetry, then observations to find out the students' initial abilities in the material used, then doing a pre-cycle with conventional learning, then implementing the Imagine technique ( Suggestion) with the first learning cycle, and ending using the Imagine technique with the second learning cycle. The results of the research show that the application of student learning in poetry writing material using the Imagine (Suggestion) technique in class VIII 3 of SMP Negeri 8 Palembang can improve student learning outcomes. In the Pre-cycle the presentation of completeness was 1%, in cycle I the presentation of completeness was 44%, and in cycle II it was 86%. Thus, the application of the Imagine (Suggestion) technique in writing poetry for class VIII 3 students at SMP Negeri 8 Palembang can improve student learning outcomes.